2020
DOI: 10.1016/j.kint.2020.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes and response to treatment in diacylglycerol kinase epsilon nephropathy

Abstract: I n 2013 recessive mutations in DGKE, which encodes diacylglycerol kinase epsilon (DGKE), were first reported to cause atypical hemolytic uremic syndrome (aHUS) 1 and nephrotic syndrome, with glomerular microangiopathy said to resemble membranoproliferative (mesangiocapillary) glomerulonephritis (MPGN) 2 (Online Mendelian Inheritance in Man #615008), though the pathophysiological mechanisms remain poorly understood. aHUS is characterized by a clinical presentation with thrombocytopenia, microangiopathic hemoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 41 publications
0
27
0
2
Order By: Relevance
“…A total of 80–94 % present with aHUS, while 6–20 % present with early-onset nephrotic syndrome and membrane proliferative glomerulonephritis (MPGN)-like features on kidney biopsy [ 3 , 4 ]. These patients who present with aHUS have a 64–70 % rate of relapse after initial remission and usually have persistent proteinuria and microscopic haematuria in between relapses [ 2 , 5 ]. For the last decade, the empirical therapy for patients diagnosed with aHUS has been eculizumab, a recombinant humanized monoclonal antibody that binds to complement component 5 (C5) to inhibit terminal complement cascade activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 80–94 % present with aHUS, while 6–20 % present with early-onset nephrotic syndrome and membrane proliferative glomerulonephritis (MPGN)-like features on kidney biopsy [ 3 , 4 ]. These patients who present with aHUS have a 64–70 % rate of relapse after initial remission and usually have persistent proteinuria and microscopic haematuria in between relapses [ 2 , 5 ]. For the last decade, the empirical therapy for patients diagnosed with aHUS has been eculizumab, a recombinant humanized monoclonal antibody that binds to complement component 5 (C5) to inhibit terminal complement cascade activation.…”
Section: Discussionmentioning
confidence: 99%
“…In the follow-up of these patients, it was noticed that the disease course and long-term outcome were similar with and without aHUS-specific therapy [ 4 ]. Brocklebank et al [ 5 ] recently reported the long-term outcomes of 16 patients with DGKE mutations. Six out of the 16 patients received plasma infusion/plasma exchange, and one patient received eculizumab during initial presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brocklebank et al outlined the genotype, phenotype, and pathophysiology of DGKE mutations associated with aHUS in 16 patients (median age 9 months) [ 50 ]. The phenotype of DGKE mutations was characterized by persistent proteinuria, at least one relapse in children, and hypertension with hematuria leading to chronic kidney failure.…”
Section: Selected Mutations and Anti-complement Factor Antibodiesmentioning
confidence: 99%
“…PGE 2 suppresses the expression of MMP-2 in Tie2Cre Dgke fl/fl mouse kidneys. DGKE nephropathy is invariably associated with proteinuria (3,25,58). Proteinuria was also present in 100% of endothelial specific Tie2-Cre Dgke fl/fl knockout mice at a later time compared with the appearance of the hematologic signs, which suggests that the filtration barrier is secondarily affected by primary endothelial abnormalities.…”
Section: Vegfr2-dependent Akt Activation Is Compromised In Dgke-knockdown Human Umbilical Vein Endothelial Cells and In Human Microvasculmentioning
confidence: 99%